The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1016/s0194-5998(03)01306-8
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic modified Lothrop procedure for the treatment of chronic frontal sinusitis: a systematic review

Abstract: The evidence base for EMLP was deemed inadequate to assess its safety and efficacy, and an audit of the procedure was recommended. Additional clinical recommendations were made regarding the development and current practice of EMLP during this audit phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 45 publications
1
57
0
1
Order By: Relevance
“…9 However, these rates were for a small series of patients ranging in age from nine to 20 years. More recently, Shirazi et al To stent or not to stent Maintaining nasofrontal patency can be problematic following the endoscopic modified Lothrop procedure.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…9 However, these rates were for a small series of patients ranging in age from nine to 20 years. More recently, Shirazi et al To stent or not to stent Maintaining nasofrontal patency can be problematic following the endoscopic modified Lothrop procedure.…”
Section: Discussionmentioning
confidence: 94%
“…A thorough knowledge of frontal sinus anatomy and proper training are required, even with the assistance of intra-operative image guidance. 9,10 Frontal osteoplastic flap versus modified Lothrop procedure As the endoscopic modified Lothrop procedure is usually performed on an out-patient basis, it is generally cheaper than treatment requiring hospital admission. Gross et al reported the cost advantage of the endoscopic modified Lothrop procedure over the frontal osteoplastic flap procedure with obliteration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An extended frontal sinusotomy (modified Lothrop procedure) is performed to expose the anterior extent of the transcribriform corridor. 41 A superior septectomy is performed to provide a panoramic view with binostril access to the ventral cribriform plate. An additional posterior septectomy can be made to allow triangulation of instrumentation through both nostrils to the surgical target.…”
Section: Endoscopic Endonasal Transcribriform Approachmentioning
confidence: 99%
“…However there are centres that would advocate more widespread use of the technique for routine work [5,25]. For cases of CRS, recurrence rates for this technique generally appear to be over 20% [25][26][27], and although some centres have reduced the actual rate of revision surgery, the recurrence rate of chronic frontal sinusitis remains above 20% [5,28]; in this respect the evidence for it to replace the osteoplastic flap as the gold standard is still lacking [29].…”
Section: Extended Endoscopic Approachesmentioning
confidence: 99%